UTILIZATION OF EVALUATION MEDIA BASED ON THE QUIZIZZ APPLICATION IN THEMATIC LEARNING AT THE 2ND GRADE - Sari, Juliana Widya; Jamaludin, Ujang; Pribadi, Reksa Adya (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
The existence of rapid technological developments at this time requires teachers to innovate in carrying out learning evaluations in order not to be monotonous. One of the innovations that can be used to provide student learning evaluation techniques is the Quizizz application. This research was conducted to know 1)the implementation of thematic learning activities; 2)the process of designing evaluation questions; 3)the learning evaluation process using the Quizizz application; and 4)the follow-up of the evaluation results. The approach of this study is qualitative, using data collection techniques like direct observation, interviews, and documentation. The results of this research indicate that 1)thematic learning activities in 2nd grade (C class) at SDN Cipondoh 03 begin with the learning planning preparation, 2)the process of designing evaluation questions through the Quizizz application begins with the preparation of the instrument questions, then the questions will be uploaded into the Quizizz application and then worked on by students, 3)the evaluation process using the Quizizz application is using student’s gadget, 4)follow-up from the results of the evaluation using the Quizizz application, through remedial and enrichment activities.